Provision of Livelihood Opportunity in the Fringe Forest: Some Experiences of Tripura - Panda, S. K. (Indian Forester, 2013)
The forest dwellers depend upon forest for meeting their livelihood requirements including fire wood, timber and other minor forest produce. But due to shrinking natural-resources and commercialization of forest products for urban utilization, forest fringe community is deprived of natural-resources which led them to frustration and anger. These have got manifested in the form of violence and unlawful activities by a section of forest dwellers. Scheduled Tribe and other Traditional Forest Dwellers (Recognition of forest rights) Act 2006 was enacted to address these issues. Tripura state under the 6th schedule of the constitution has established the Tripura Tribal Area Autonomous District and empowered the fringe forest communities to govern themselves and to protect and preserve their culture, customs and traditions. Present article described the various steps taken by the Tripura Government to address various issues for the welfare of forest dwellers for creating "Win-Win" situation.